Experimental investigation on the flexural behavior of concrete reinforced by various types of steel fibers - Zhao, Liangping; Chen, Gang; Huang, Chunshui (Frontiers in Materials, 2023)
The effects of fiber type and aspect ratio on the flexural behavior of steel fiber reinforced concrete (SFRC) were investigated. The milled fiber (M), corrugated fiber (C) and three hooked fibers with aspect radios of 45 (HA), 55 (HB), and 65 (HC) were adopted in this study. Two volume fractions (0.4% and 1.0%) of steel fiber and two compressive strengths (normal and high strengths) of matrix were considered. The results show that the hooked fiber reinforced beams performed the best flexural load-deflection response compared to milled fiber and corrugated fiber reinforced beams, and exhibited an increasing trend of flexural performance as the fiber aspect ratio increased. Epeak (the energy absorption capacity up to the peak point) of all test series are similar, while the order of EL/m (the energy absorption capacity up to the points L/600, L/300, L/200 and L/150) based on fiber type and aspect ratio is respectively as follows: HB fiber > C fiber > M fibers, HC fiber > HB fiber > HA fiber. The EL/150 of high strength concrete with 1.0% HB-fibers is 2.67 and 3.05 times higher than that with 1.0% M-and C-fibers, respectively. The EL/150 of high strength concrete with 1.0% HC-fibers is 1.75 and 1.17 times higher than that with 1.0% HA-and HB-fibers, respectively. The differences of flexural behavior between specimens with different fibers for high strength matrix are more remarkable compared to the normal strength matrix.